2021
DOI: 10.3389/fnut.2021.591964
|View full text |Cite
|
Sign up to set email alerts
|

Negative Association Between Mediterranean Diet Adherence and COVID-19 Cases and Related Deaths in Spain and 23 OECD Countries: An Ecological Study

Abstract: In December 2019, the severe acute respiratory syndrome coronavirus 2 (SARS-Cov2) emerged in Wuhan, China, sparking the Coronavirus disease 2019 (COVID-19) pandemic. The high prevalence of nutrition-related COVID-19 risk factors including obesity, type 2 diabetes, and hypertension, suggests that healthy dietary approaches may mitigate COVID-19 related outcomes and possibly SARS-CoV-2 infection. Based on the fundamental role of nutrition in immune function and the well-documented association between Mediterrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 71 publications
7
47
1
2
Order By: Relevance
“…Beyond the association of the food intake quality and intense physical activity with 25(OH)D sufficiency identified in our report, according to an ecological study by Greene, et al [43], adherence to a healthy dietary pattern is associated with fewer COVID-19 cases and deaths. In particular, the previously mentioned study analyzed adherence to the Mediterranean diet (rich in fresh vegetables and fruits, whole grains, nuts, fish, and extra virgin olive oil) where well-being factors such as income, education, and life satisfaction increased the strength of the association [43,44]. Greene, et al suggest that this result is due to the anti-inflammatory and chronic-disease reducing effects related to the intake of foods included in the Mediterranean diet [43].…”
Section: Discussionsupporting
confidence: 38%
See 1 more Smart Citation
“…Beyond the association of the food intake quality and intense physical activity with 25(OH)D sufficiency identified in our report, according to an ecological study by Greene, et al [43], adherence to a healthy dietary pattern is associated with fewer COVID-19 cases and deaths. In particular, the previously mentioned study analyzed adherence to the Mediterranean diet (rich in fresh vegetables and fruits, whole grains, nuts, fish, and extra virgin olive oil) where well-being factors such as income, education, and life satisfaction increased the strength of the association [43,44]. Greene, et al suggest that this result is due to the anti-inflammatory and chronic-disease reducing effects related to the intake of foods included in the Mediterranean diet [43].…”
Section: Discussionsupporting
confidence: 38%
“…In particular, the previously mentioned study analyzed adherence to the Mediterranean diet (rich in fresh vegetables and fruits, whole grains, nuts, fish, and extra virgin olive oil) where well-being factors such as income, education, and life satisfaction increased the strength of the association [ 43 , 44 ]. Greene, et al suggest that this result is due to the anti-inflammatory and chronic-disease reducing effects related to the intake of foods included in the Mediterranean diet [ 43 ]. Likewise, Tavakol, et al [ 45 ] reported that patients with a healthy diet pattern presented a lower severity of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…2, 4) correlate with GDP [9,30], therefore it is vital to find answer for the question: which component of wealthy being is the risk factor for SARS-CoV-2 infection process? In some investigations was observed a negative relationship between COVID-19 associated death rates and using of highly recommended healthy Mediterranean diet across many countries [42][43][44][45][46]. In these investigations was concluded that diet can be important factor among others affecting of current corona-virus pathogenesis.…”
Section: Quantitate Evaluation Of Socioeconomic Factors and Progress Of Virus Infectionmentioning
confidence: 99%
“…More than a few scientific groups have investigated the effects of diet on COVID-19 disease progression and mortality in distinct nations [39,40,42,43,45,46,48]. Kontis and coauthors [27] investigated data from the first wave of pandemic in 21 industrial countries and shown that magnitude of mortality was heterogeneous in this group of patients.…”
Section: Nutrition Habits and Outcomes Of Virus Epidemic In Different Regions Of Five Continentsmentioning
confidence: 99%
“…Ecological studies of COVID-19 report favorable correlations with specific vegetables and dietary patterns, such as the Mediterranean diet [8][9][10]. Some dietary supplements were found to have an association with SARS-CoV-2 infection [11].…”
Section: Introductionmentioning
confidence: 99%